The Case for Conserving Monsters: Rosemarie Garland-Thomson and the Body of Christ - Parks, Benjamin N. (Journal of disability & religion, 2020)
Rosemarie Garland-Thomson has made a moving case for what she calls conserving the generative resourcefulness of disability. She thinks that in showing all the good that various disabilities and the people with them make to the world she is also showing the inherent moral value of people with disabilities. However, her argument is ultimately utilitarian because it lacks a metaphysical referent. In this paper, I offer the Body of Christ as a way of showing the resourcefulness of disability and people with disabilities and securing their inherent moral value.